Phytochemicals and proteomic profiling of ethyl acetate of M. micrantha extract treated hypercholesterolemic rats - Ibrahim, Azlinda; Shafie, Nurul Husna; Mohd Esa, Norhaizan; Shafie, Siti Raihanah; Bahar, Hasnah; Mohamad Zainal, Nurul Hayati (Universiti Putra Malaysia Press, 2024)
Introduction: Mikania micrantha possess potent anti-hypercholesterolemic properties. However, the phytochemicals of M. micrantha and protein regulation that led to its hypocholesterolemia effects are limited. The aim of this study is to investigate the phytochemicals and proteomic profiling of liver samples from hypercholesterolemic rats that were treated with M. micrantha extract. Materials and methods: The identification of phytochemicals in the ethyl acetate of M. micrantha stem (EAMMS) extract was conducted through the liquid chromatography quadrupole time-of-flight mass spectrometry (LC-QToF-MS). The rats were divided into two distinct groups: a normal group (NC) and a group induced with hypercholesterolemia, both of which were observed for an initial duration of four weeks. Following the completion of the fourth week of the induction period, the rats were divided into five groups: 1% high cholesterol diet (HCD), 1% HCD + Simvastatin (10 mg/kg of body weight (BW)), 1% HCD + EAMMS (50 mg/kg/BW), 1% HCD + EAMMS (100 mg/kg/BW) and 1% HCD + EAMMS (200 mg/kg/BW) for another 4 weeks of treatment periods. The LC-MS/MS analysis was conducted on liver tissue to identify differentially expressed proteins. Results: The phytochemicals were identified in the EAMMS extract, including theobromine, ishwarol, pheophorbides, and dihydromikanolide. In association with hypercholesterolemia, a total of 26 differentially expressed proteins were identified. Among these proteins, nine proteins exhibited elevated levels, whereas 17 showed downregulation, which mainly involved in lipid metabolism pathway. Conclusion: Overall, these results provide understanding on the molecular targets of EAMMS extract, which could be used for further study on the putative anti-hypercholesterolemic properties.